Odpowiedzialność odszkodowawcza organów administracji publicznej za nieprawidłową realizację kompetencji prawotwórczych - Lewicka, Renata (Acta Universitatis Lodziensis. Folia Iuridica, 2009)
The result of the constitutional principle of democratic state of law is that an individual should not bear the consequences of defective standards existing in the legal system but should be entitled to claim damages resulting from the legislation public authorities. Legal regulations of the civil liability of public authorities are characterized, as regards normative delicts, including both defective law-making activity and the so-called legislative omission. The conditions of civil liability of public administrative authorities and procedure of compensation claims are discussed in detail in this paper.